Four sisters and their implicatures an analysis of the relationship between conversational implicatures and Filipino communication - Jacob, Frances Therese B. (College of Arts and Letters, University of the Philippines Diliman, 2018)
The purpose of this undergraduate thesis is to employ the analysis of the conversational implicatures present in the film Four Sisters and A Wedding to investigate the characterization of the female Filipino characters and the film's representation of a Filipino communication style. To be specific, this study aims to look into the collaborative and competitive speech strategies that are used by the titular sisters in their manifestation or rejection of certain Filipino values and relational standards, in order to arrive at conclusions regarding the subsequent construction and depiction of features of Filipino communication present in the film. In doing so, the researcher makes use of a conceptual framework that argues for an interrelationship among H.P. Grice's Cooperative Principle and notion of implicature, Deborah Tannen and Jennifer Coates' respective theories on the relativity of linguistic strategies, Dell Hymes' SPEAKING model, Virgilio Enriquez' kapwa theory, and F. Landa Jocano's pamantayan system within a communication schema. The data consists of isolated utterances from the communicative exchanges in the film in which the Salazar sisters participate wherein the use of conversational implicatures is evident. The findings of this research show that the linguistic strategies employed by the four sisters through their use of conversational implicatures challenge the essentialist view of competitive and collaborative speech styles, given the relativity, ambiguity, and polysemy of their speech choices. In this way, the characters uphold confrontive values in achieving cooperation and solidarity, while their speech underlines that gender cannot be the sole identity category considered in the interpretation of competition and collaboration.